Coral Reef Substrate Coverage in Taka Bonerate National Park - Sanova, Aulia Seto Sandhi; Nugroho, Hanityo Adi; Mahardini, Angka; Agus, Elsa Lusia; Rahman, Saleh; Sutanto, Steven; Retawimbi, Aditano Yani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Coral reef monitoring using Reef Check Method has been widely applied for conservation acts due to its handy protocols. This study aims to evaluate the coral reef conditions in the zonal areas of Taka Bonerate National Park by analyzing the substrate composition of its waters. Conducted in November 2023 using the Reef Check method, the research focused on four stations: Tinabo Besar, Tinabo Kecil, Tinanja, and Taka Lasalimu. The substrate composition was categorized into living and non-living substrates at depths of 5 and 10 meters. At 5 meters depth, the highest percentage of living substrate cover, specifically hard coral (HC), was recorded at Tinanja (74%), while the highest non-living substrate cover, dead coral/rubble (RB), was observed at Tinabo Kecil (38%). At 10 meters depth, Tinanja again showed the highest living substrate cover (HC, 40%), whereas Tinabo Kecil had the highest non-living substrate cover (RB, 41%). The findings indicate that the coral reef Substrate in the TBNP zonal area is in good condition, although some locations show damage suspected to be caused by environmentally unfriendly fishing practices. This can serve as a reference for the future management of coral reefs in TNTBR. Further research is needed to comprehensively complete the data on coral reef health, such as data on reef fish and associated invertebrates.